2010
DOI: 10.1159/000317092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCl 0.9% Infusion during Plasmapheresis on IgG Content in Plasma

Abstract: Background: The aim of this study was to evaluate the influence of an infusion of NaCl 0.9% 500 ml during preparatory plasmapheresis or apheresis on the immunoglobulin G (IgG) content in separated plasma. Methods: 32 donors of plasma were studied in a crossover design after informed consent on one day without NaCl 0.9% 500 ml during apheresis and on another day with infusion of NaCl 0.9% 500 ml during apheresis. Infusion of NaCl 0.9% 500 ml was given step by step in divided doses after each cycle through the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(43 citation statements)
references
References 6 publications
(5 reference statements)
4
39
0
Order By: Relevance
“…A recent study reported a significant hemodilution effect of 5% in plasma IgG when 500 mL of saline was infused at intervals during plasmapheresis, during which 760 mL of plasma was collected 12 . Taken together with our findings; the data from this study suggest that intraprocedure infusion of saline can result in hemodilution of the collected plasma components.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study reported a significant hemodilution effect of 5% in plasma IgG when 500 mL of saline was infused at intervals during plasmapheresis, during which 760 mL of plasma was collected 12 . Taken together with our findings; the data from this study suggest that intraprocedure infusion of saline can result in hemodilution of the collected plasma components.…”
Section: Discussionsupporting
confidence: 84%
“…Thirty‐two regular donors of plasma were initially studied in a crossover design to evaluate the influence of a saline infusion during DP on immunoglobulin (IgG) content in collected plasma . The study was performed according to the standards of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…As no study has been published on the distribution of citrate in DP between donor and retained plasma, we re‐analyzed data initially collected for a study published in 2010 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the influence of an infusion of 500 ml 0.9% NaCl during preparatory plasmapheresis (PP) on separated plasma has been studied recently [1,2], there are only limited data on the changes in hemoglobin (HGB) concentration and hematocrit (HCT) values in donor blood during and after PP without or with an infusion of saline solution. Increases of HGB concentration and HCT might be the cause of the diminished blood flow that is sometimes seen at the end of plasma donations, and could be dangerous for donors who have a risk for venous thromboses or ischemic infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of 500 ml 0.9% NaCl is a commonly accepted practice to prevent hypotensive events during PP or apheresis. The disadvantage may be a dilution effect of infused saline solution on the separated plasma by 5% [1]. However, the benefits to donor safety and satisfaction are compelling reasons to implement saline infusion during plasmapheresis [2].…”
Section: Introductionmentioning
confidence: 99%